2009
DOI: 10.5194/acp-9-7101-2009
|View full text |Cite
|
Sign up to set email alerts
|

Regional modelling of tracer transport by tropical convection – Part 2: Sensitivity to model resolutions

Abstract: Abstract. The general objective of this series of two papers is to evaluate long duration limited-area simulations with idealised tracers as a possible tool to assess the tracer transport in chemistry-transport models (CTMs). In this second paper we analyse the results of three simulations using different horizontal and vertical resolutions. The goal is to study the impact of the model spatial resolution on convective transport of idealized tracer in the tropics. The reference simulation (REF) uses a 60 km hor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In order to simulate halogen chemistry in volcanic plumes, we have added 16 halogen species and 54 reactions to the chemical scheme including photolysis and gas-phase and heterogeneous reactions. The gas-phase constant rates and photolysis cross sections are from the Jet Propulsion Laboratory (Sander et al, 2006) and the International Union of Pure and Applied Chemistry (Atkinson et al, 2007). The heterogeneous reactions include the hydrolysis of BrONO 2 and the reaction of HOBr + X − (aq) + H + (aq) , where X = Br or Cl on sulfate aerosol.…”
Section: Model Chemistrymentioning
confidence: 99%
“…In order to simulate halogen chemistry in volcanic plumes, we have added 16 halogen species and 54 reactions to the chemical scheme including photolysis and gas-phase and heterogeneous reactions. The gas-phase constant rates and photolysis cross sections are from the Jet Propulsion Laboratory (Sander et al, 2006) and the International Union of Pure and Applied Chemistry (Atkinson et al, 2007). The heterogeneous reactions include the hydrolysis of BrONO 2 and the reaction of HOBr + X − (aq) + H + (aq) , where X = Br or Cl on sulfate aerosol.…”
Section: Model Chemistrymentioning
confidence: 99%
“…265-165 hPa) altitude matched the measurements best. Arteta et al (2009a) used an online regional model, CATT-BRAMS, to investigate the sensitivity of tropical tracer transport to the convective parameterisation, and Arteta et al (2009b) evaluated the effect of resolution on the simulated tracer distributions, showing that the higher resolution versions of their model produce more convective transport which reaches higher altitudes. Various studies (Wild and Prather, 2006;Rind et al, 2007;Deng et al, 2004) have shown that increases in horizontal and vertical resolution improve the skill of the model in predicting tracer transport by convection.…”
Section: Introductionmentioning
confidence: 99%
“…265-165 hPa) matched the measurements best. Arteta et al (2009a) used an online regional model, CATT-BRAMS, to investigate the sensitivity of tropical tracer transport to the convective parameterisation, and Arteta et al (2009b) evaluated the effect of resolution on the simulated tracer distributions, showing that the higher resolution versions of their model exhibited more efficient convective transport, reaching higher altitudes. Various studies (Deng et al, 2004;Wild and Prather, 2006;Rind et al, 2007) have shown that increased horizontal and vertical resolution improves the skill of the model in predicting tracer transport by convection.…”
Section: Introductionmentioning
confidence: 99%